Association Between Orthonasal Olfaction and Chemosensory Perception in Patients With Smell Loss - Liu, David T. (Laryngoscope, 2020)
OBJECTIVES: Self‐ratings seem to be the most effortless strategy for assessment of patients' chemical senses. Notably, although flavor perception strongly relies on olfaction, the relationship between self‐reported flavor perception and orthonasal olfactory tests have hitherto not been considered. The aim of this study was to investigate the relationship between self‐perceived olfactory function (SO), taste (ST), and flavor perception (SF) and smell test results in patients with olfactory dysfunction (OD). METHODS: We included 203 patients with quantitative OD. Group comparison, bivariate correlation, and ordinal logistic regression were employed to quantify the relationships between predictor variables (age, gender, reason for OD, and orthonasal olfaction—summed scores of threshold, discrimination, and identification [TDI]) and outcomes of SO and SF (“impaired,” “average,” or “good”). RESULTS: Group comparison revealed significant differences between SO and SF (P < .001). Stronger correlations were found between SO and TDI (r = 0.64), compared to SF and TDI (r = 0.27). No relevant correlation was found between ST and TDI (r = 0.10). Higher TDI was associated with odds of higher SO in univariate (odds ratio = 1.25) and multivariable analyses (adjusted odds ratio = 1.23), and both models showed good fit of data. Conversely, regression models on the associations between TDI and changes in SF did not meet the assumption of goodness of fit. CONCLUSION: We found that higher orthonasal olfactory performance was associated with odds of higher SO in patients with OD, even after controlling for olfactory‐relevant factors. To the contrary, similar models based on flavor perception failed to describe these relationships. This indicates for SF and ST to be less represented by the TDI compared to SO. LEVEL OF EVIDENCE: 4 Laryngoscope, 130:2213–2219, 2020